2003
DOI: 10.1046/j.1600-0854.2003.00144.x
|View full text |Cite
|
Sign up to set email alerts
|

Compromise of Clathrin Function and Membrane Association by Clathrin Light Chain Deletion

Abstract: While clathrin heavy chains from different species are highly conserved in amino acid sequence, clathrin light chains are much more divergent. Thus clathrin light chain may have different functions in different organisms. To investigate clathrin light chain function, we cloned the clathrin light chain, clcA, from Dictyostelium and examined clathrin function in clcA-mutants. Phenotypic deficiencies in development, cytokinesis, and osmoregulation showed that light chain was critical for clathrin function in Dict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 32 publications
1
68
0
3
Order By: Relevance
“…We expressed GFP-Ap2A1 in cells with either disrupted clathrin light chain (clc-) (Wang et al, 2003) or disrupted clathrin heavy chain (chcA-) (Ruscetti et al, 1994). TIR-FM imaging of GFP-Ap2A1 in clc-cells showed that AP2 was able to localize to membrane puncta that behaved with similar dynamics to wild-type cells ( Fig.…”
Section: Intracellular Localization and Dynamics Of Clathrin And Ap2 mentioning
confidence: 99%
See 2 more Smart Citations
“…We expressed GFP-Ap2A1 in cells with either disrupted clathrin light chain (clc-) (Wang et al, 2003) or disrupted clathrin heavy chain (chcA-) (Ruscetti et al, 1994). TIR-FM imaging of GFP-Ap2A1 in clc-cells showed that AP2 was able to localize to membrane puncta that behaved with similar dynamics to wild-type cells ( Fig.…”
Section: Intracellular Localization and Dynamics Of Clathrin And Ap2 mentioning
confidence: 99%
“…Genetic deletions of clathrin in Dictyostelium have revealed its importance for macropinocytosis, cytokinesis, development and osmoregulation (O'Halloran and Anderson, 1992;Ruscetti et al, 1994;Niswonger and O'Halloran, 1997a;Niswonger and O'Halloran, 1997b;Wang et al, 2003). Given that clathrin functions at numerous membrane transport steps, it has been difficult to resolve whether CME from the plasma membrane is important for any of these processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clathrin-deficient Dictyostelium cells show dramatic morphological and functional defects of the CV (O'Halloran and Anderson, 1992;Wang et al, 2003). Deletion of the apm1 gene encoding the medium subunit of the clathrin adaptorprotein AP-1 also results in the absence of a characteristic CV (Lefkir et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Additional work will be needed to sort out whether the position of helix 7j depends at all on the C-terminus of CLC. The fact that CLC knockouts in Saccharomyces cerevisiae destroy the trimeric clathrin structure (70,71), while the clathrin structure in Dicytostelium is unaffected by knocking down CLC (73), suggests that any CLC role will likely be organism specific.…”
Section: Clathrin Detrimerization and Nuclear Localizationmentioning
confidence: 99%